1982
DOI: 10.1159/000465373
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Acetaminophen in Donated Blood

Abstract: Acetaminophen levels were determined in 1,176 sera separated from donated blood. The analysis was performed by both a colorimetric method and by high performance liquid chromatography. 6.12% of the samples contained acetaminophen levels ranging from 18 to 58 µg/ml. The possible clinical significance of such a high incidence of this drug among healthy blood donors is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, the latter no longer represents the standard preparation of modern blood banking [1,8,9,10]. On the basis of the results of Ferner et al [7] and taking into account further published evidence [8,9,11,14,15,16,18,19,20], we have proposed two approaches to deal with the problem of donor medication. Advantages of the ®rst approach, which guarantees a reduction of any donor medication to the level of 3% of the therapeutic drug concentration, are its simplicity, its wide safety margin and its easy applicability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the latter no longer represents the standard preparation of modern blood banking [1,8,9,10]. On the basis of the results of Ferner et al [7] and taking into account further published evidence [8,9,11,14,15,16,18,19,20], we have proposed two approaches to deal with the problem of donor medication. Advantages of the ®rst approach, which guarantees a reduction of any donor medication to the level of 3% of the therapeutic drug concentration, are its simplicity, its wide safety margin and its easy applicability.…”
Section: Discussionmentioning
confidence: 99%
“…A careful interview on drug intake constitutes an essential part of any donor ®tness examination. However, the assumption that potential blood donors report their drug intake properly has been questioned repeatedly [3,4,5,18,19,20,21]. Mahnovski et al have shown that in 15% of random blood donors, drugs or their metabolites were assessable in the urine, despite reporting no drug use on being questioned [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation